Improvement of Cold Filter Plugging Point of Jatropha-Corn Biodiesel Blend Using Acrylic Copolymer - Ho, May Yun (Universiti Teknologi PETRONAS, 2012)
Theaim of this study is to investigate the influence of fatty acid compositions in biodiesel on some parameters such as the oxidation stability, iodine value and cold flow properties. Edible oil is represented byrefined corn oil and non-edible oil represented by jatropha curcas oil. In order to overcome the shortcomings of jatropha-corn biodiesel, acrylic copolymer is introduced as a Cold Flow Improvers (CFIs) additive to reduce the cold filter plugging point (CFPP). Crude jatropha oil was pre-treated to minimize the high free fatty acid content. The treated jatropha oil and refined corn oil were then transesterificated using sodium methoxide,CH3ONa as catalyst at standard reaction conditions (reaction time, 1.5 h; weight of catalyst 1 wt.% of initial oil weight; molar ratio methano:oil/ 6:1; reaction temperature, 64°C) to produce jatropha methyl ester (JME) and corn methyl ester (CME) respectively. The biodiesel is then blended at different mass ratios. Each jatropha-corn biodiesel blend parameters such oxidation stability, iodine value, density, calorific value, fatty acid content and cold flow properties are investigated. The biodiesel was tested accordingly to the standard UNEEN 14214 for quality assurance. Results show that ratio blend CME:JME (20:80) gives 6.42 hours of oxidation stability and -2°C for CFPP which complies with the EN 14214 standards. Acrylic copolymer as CFI is then added to the same blend ratio to reduce the CFPP. CFI successfully reduced the CFPP from -2°C to -6°C which gives better cold flow properties to the corn-jatrophabiodiesel blend.